Radio and X-ray variability in the Seyfert galaxy NGC 4051 - Jones, S.; McHardy, I.; Moss, D.; Seymour, Nick; Breedt, E.; Uttley, P.; Körding, E.; Tudose, V. (2011)
We present intensive quasi-simultaneous X-ray and radio monitoring of the narrow line Seyfert 1 galaxy NGC 4051, over a 16-month period in 2000–01. The X-ray observations were made with the Proportional Counter Array on the Rossi Timing X-ray Explorer (RXTE) and radio observations were made at 8.4 and 4.8 GHz with the Very Large Array (VLA). In the X-ray band NGC 4051 behaves very much like the analogue of a Galactic black hole binary (GBH) system in a ‘soft state’. In such systems, there has so far been no firm evidence for an active, radio-emitting jet like those found in ‘hard-state’ GBHs. VLBI observations of NGC 4051 show three well-separated compact components almost in a line. This structure resembles the core and outer hot spots seen in powerful, jet-dominated, extragalactic radio sources and, although no jet is visible in NGC 4051, suggests that a weak jet may exist. However it has not previously been clear whether the nucleus is currently active in the radio band and whether there is any link between the radio and X-ray emission processes. In order to evaluate observations in the context of survey selection effects, we examine the temperature distribution of four ULIRG samples from IRAS, Spitzer/MIPS, BLAST and SCUBA. We find that the lack of cold ULIRGs in the local (z ≤ 0.1) Universe is not a consequence of the selection and that the range of ULIRG temperatures seen locally is only a subset of a much larger range which exists at high redshift. We demonstrate that the local luminosity–temperature (L–T) relation, which indicates that more luminous sources are also hotter, is not applicable in the distant Universe when extrapolated to the ULIRG regime, because the scatter in observed temperatures is too large. Finally, we show that the difference between the ULIRG temperature distributions locally and at high redshift is not the result of galaxies becoming colder due to an L–T relation which evolves as a function of redshift. Instead, they are consistent with a picture where the evolution of the infrared luminosity function is temperature dependent, i.e. cold galaxies evolve at a faster rate than their warm counterparts.Radio monitoring of the core of NGC 4051 is complicated by the presence of surrounding extended emission and by the changing array configurations of the VLA. Only in the A configuration is the core reasonably resolved. We have carefully removed the differing contaminations of the core by extended emission in the various arrays. The resulting lightcurve shows no sign of large amplitude variability (i.e. factor 50 per cent) over the 16-month period and is consistent with being constant. Within the 6 A configuration observations where we have greatest sensitivity we see marginal evidence for radio core variability of ~25 per cent (~0.12 mJy at 8.4 GHz) on a 2-week time-scale, correlated with X-ray variations. These percentage variations are similar to those of the Seyfert galaxy NGC 5548, which is 10 times brighter. Even if the radio variations in NGC 4051 are real, the percentage variability is much less than in the X-ray band. Within the B configuration observations, although sensitivity is somewhat reduced, there is no sign of correlated X-ray/radio variability.Radio monitoring of the core of NGC 4051 is complicated by the presence of surrounding extended emission and by the changing array configurations of the VLA. Only in the A configuration is the core reasonably resolved. We have carefully removed the differing contaminations of the core by extended emission in the various arrays. The resulting lightcurve shows no sign of large amplitude variability (i.e. factor 50 per cent) over the 16-month period and is consistent with being constant. Within the 6 A configuration observations where we have greatest sensitivity we see marginal evidence for radio core variability of ~25 per cent (~0.12 mJy at 8.4 GHz) on a 2-week time-scale, correlated with X-ray variations. These percentage variations are similar to those of the Seyfert galaxy NGC 5548, which is 10 times brighter. Even if the radio variations in NGC 4051 are real, the percentage variability is much less than in the X-ray band. Within the B configuration observations, although sensitivity is somewhat reduced, there is no sign of correlated X-ray/radio variability.